Questionnaire-Based Assessment of Executive Functioning: Psychometrics - Castellanos, Irina (Appl Neuropsychol Child, 2016)
The psychometric properties of the Learning, Executive, and Attention Functioning (LEAF) scale were investigated in an outpatient clinical pediatric sample. As a part of clinical testing, the LEAF scale, which broadly measures neuropsychological abilities related to executive functioning and learning, was administered to parents of 118 children and adolescents referred for psychological testing at a pediatric psychology clinic; 85 teachers also completed LEAF scales to assess reliability across different raters and settings. Scores on neuropsychological tests of executive functioning and academic achievement were abstracted from charts. Psychometric analyses of the LEAF scale demonstrated satisfactory internal consistency, parent-teacher inter-rater reliability in the small to large effect size range, and test-retest reliability in the large effect size range, similar to values for other executive functioning checklists. Correlations between corresponding subscales on the LEAF and other behavior checklists were large, while most correlations with neuropsychological tests of executive functioning and achievement were significant but in the small to medium range. Results support the utility of the LEAF as a reliable and valid questionnaire-based assessment of delays and disturbances in executive functioning and learning. Applications and advantages of the LEAF and other questionnaire measures of executive functioning in clinical neuropsychology settings are discussed.